Healthcare Waste Management in Low Resource Countries - Nigerian Experience - Sowande, Abimbola Oludotun; Amaefule, Kelechi Enweruzo; Pearson, Jennifer; Iyortim, Isa (International Journal of Infection Control, 2014)
Background: Health care waste management (HCWM) is central to infection prevention and control (IPC) as poor management exposes health care workers, waste handlers, and communities to infections and injuries. A 2004 National injection safety (IS) and HCWM survey revealed that HCWM practices were grossly inadequate and included poor segregation as well as open, unsupervised dumping of waste. Aliyu et al (2006) documented that 26.5% of HCW in the Federal Capital Territory (FCT) was hazardous. Intervention: In-country capacity was built through advocacy, training, and supportive supervision by PEPFAR funded AIDSTAR-One (previously Making Medical Injections Safer) project, . Though political support differs across states, Lagos state leads in support towards strengthening their HCWM systems and conduct annual HCWM Summit to create awareness across the country to promote best practices. The 2004 survey showed 65% of health facilities (HF) demonstrated improper management of HCW, whereas a follow-up comparative study at AIDSTAR-One focal sites showed significant improvements including increase in facilities without presence of loose infectious waste, up from 50% to 70% after one year intervention. HFs with waste segregation in color coded bins at point of generation rose from 0% to 80% and loose sharps around facilities decreased from 74% to 66%. GIS mapping of HCW treatment equipment in Nigeria was conducted in 2012 to aid stakeholders in HCWM planning. Advocacy for national intervention resulted in approval of National HCWM Policy on the 4th of September 2013. Challenges: Approval process for the National HCWM Policy lengthy due to bureaucracy and unstable political climate. There is weak central direction in strengthening the HCWM systems at all levels, and segregation commodities are inadequate due to poor budgetary allocation. Conclusion: Healthcare waste management has shown a remarkable improvement and continued improvement is expected with the passage of the National HCWM Policy.